Detection of Atta Capiguara Ant Nests from aerial images using Random Forest Classifiers - Almeida, Tayná Bertacine De; Hernandes, André Carmona (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
In the last 40 years, Brazilian agricultural production and productivity have had significant increases. Agribusiness has been strongly recognised in the growth of the Brazilian Gross Domestic Product, which has resulted in investments and technological advances in the agricultural sector. With these technological advances came precision agriculture. As part of the advances in precision agriculture, Unmanned Aircraft are gaining more and more space, given their flexibility of use and diversity of applications. At the same time, the use of computer vision and machine learning brings analysis technologies that further optimise processes, such as pasture mapping and pest detection. And when it comes to crop pests, leaf-cutter ants come to mind. The direct and indirect damage that leaf-cutting ants can cause amounts to billions of dollars worldwide. The leaf-cutting ant, known as Sauva, is one of the insects that causes most damage to pastures in southeastern Brazil, even competing with cattle for grass. Pest control is of paramount importance for the growth of agricultural production, therefore, this article presents the proposal for the development of an algorithm capable of detecting anthills. Based on recent technological advances and cost reduction, the proposed detection was performed using an unmanned aerial vehicle with an integrated conventional RGB camera and an algorithm, based on computer vision and machine learning. The proposed classification algorithm was Random Forest and it presented an accuracy of approximately 70%. The application of computer vision and quadrotors in the detection of ant nests represented a good opportunity to boost precision agriculture and pest control in the field.